Monitoring Suhu dan Kelembaban Tanah Serta Penyiraman Otomatis Buah Naga Berbasis AWS - Dwi Suci Amelia; Hidra Amnur; Hanriyawan Adnan Mooduto (SOTVI - Society of Visual Informatics, 2021)
Indonesia is an agricultural country that has various types of horticultural plants, one of which is dragon fruit. Dragon fruit is a plant that requires extra care by paying special attention to its growth factors. One of the dragon fruit growth factors is temperature and soil moisture. Dragon fruit will grow well at temperatures ranging from 26-36 degrees Celsius. In addition, this plant must grow on soil that is always moist and not dry and not waterlogged. This is used to avoid rotting stems or dead plants. Therefore, this plant requires monitoring of soil temperature and humidity so that continuous monitoring can be carried out. This plant also requires automatic watering to keep the soil moist.